Age-Specific Associations of Reduced Estimated Glomerular Filtration Rate with Concurrent Chronic Kidney Disease Complications - Bowling, C. Barrett (American Society of Nephrology, 2011)
SUMMARY: BACKGROUND AND OBJECTIVES: It has been suggested that moderate reductions in estimated GFR (eGFR) among older adults may not reflect chronic kidney disease (CKD). DESIGN, SETTING, PARTICIPANTS, & MEASUREMENTS: We examined age-specific (<60, 60 to 69, 70 to 79, and ≥80 years) associations between eGFR level and six concurrent CKD complications among 30,528 participants from the National Health and Nutrition Examination Survey (NHANES) 1988 to 1994 and 1999 to 2006 (n = 8242 from NHANES 2003 to 2006 for hyperparathyroidism). Complications included anemia (hemoglobin <12 g/dl women, <13.5 g/dl men), acidosis (bicarbonate <22 mEq/L), hyperphosphatemia (phosphorus ≥4.5 mg/dl), hypoalbuminemia (albumin <3.5 mg/dl), hyperparathyroidism (intact parathyroid hormone ≥70 pg/ml), and hypertension (systolic/diastolic BP ≥140/90 mmHg or antihypertensive use). RESULTS: Among participants ≥80 years old, compared with those with estimated GFR (eGFR) ≥60 ml/min per 1.73 m(2), the multivariable adjusted prevalence ratios (95% confidence interval) associated with eGFR levels of 45 to 59 and <45 ml/min per 1.73 m(2) were 1.39 (1.11 to1.73) and 2.06 (1.59 to 2.67) for anemia, 1.33 (0.89 to 1.98) and 2.47 (1.52 to 4.00) for acidosis, 1.11 (0.70 to 1.76) and 2.16 (1.36 to 3.42) for hyperphosphatemia, 2.04 (1.39 to 3.00) and 2.83 (1.76 to 4.53) for hyperparathyroidism and 1.09 (1.03 to 1.14), and 1.12 (1.05 to 1.19) for hypertension, respectively. Higher prevalence ratios for these complications at lower eGFR levels were also present at younger ages. Reduced eGFR was associated with hypoalbuminemia only for adults <70. CONCLUSIONS: Reduced eGFR was associated with a higher prevalence of several concurrent CKD complications, regardless of age.